Pengaruh Struktur Modal, Profitabilitas dan Ukuran Perusahaan Terhadap Nilai Perusahaan pada Perusahaan Sektor Transportasi yang Terdaftar di BEI Periode 2019-2021 - Firdaus, Rifqi Adhitama; Artati, Dwi (LP3M Universitas Putra Bangsa, 2023)
This study aims to determine the effect of capital structure, profitability and firm size to firm value. The variable of company value is proxied by Price to Book Value (PBV), capital structure policy proxies with Debt to Equty Ratio (DER), profitability proxies with Return on Asset (ROA) and firm size is measured using the formula Ln (Total Asset). The population in this study is a transportation company listed on the Indonesia Stock Exchange (BEI) in 2019-2021 as many as 12 companies. The sample of research is 11 companies with purposive sampling method. The method used in this research is quantitative method. Data analysis used multiple linear regression analysis with SPSS 25 program. The result showed that capital structure had positive effect on firm value, profitability had negative effect on company value and firm size had negative effect on firm value simultaneously.